The construction methodology in the teaching of natural sciences: Proposal for continuing education beginning teachers in primary education (Papeles, 2014)
This paper is presented an accompanying proposal in the first steps of new teachers at the Training Institute de Bariloche, Argentina (continuing education). In addition, a reflection on the productions and the evaluation done by teachers was written. This program proposes to promote higher levels of professionalism from the first steps of employment, to provide support tools that facilitate teaching practices in line with the theoretical and methodological foundations of initial and individual institutional requirements where they are inserted.
Keywords: beginners Teachers; science education; construction Methodology